Utilization of Concentrated Buttermilk in Functional Processed Cheese Manufacturing and Studying Some of its Physicochemical Properties - S. Doosh, Kifah; A. Alhusyne, Layla; N. Almosawi, Baha (Pakistan Journal of Nutrition, 2013)
This investigation was carried out to study the effect of utilizing concentrate butter milk (CBM) which prepared by exposure of butter milk to heat treatment (100 ºC) for different time 15, 30 and 60 min, treatments T1, T2 and T3 respectively in preparing of processed cheese (PC), in addition to control treatment (C) which PC prepared without CBM. The CBM was added to base blend during cooking stage. The prepared samples were analyzed for chemical and sensory properties, at zero time and during storage period of 4 weeks at 6±1ºC. The results reveled that there were significant differences in the chemical composition for fat%, protein%, ash% and moisture% and no significant differences in sensory evaluation which conducted at zero time for color, taste and flavor, texture and bitterness between control and treated PC, while PC treatments stay more acceptable than control PC at all storage periods, especially cheese treatments T2 and T3. The obtained results showed that T2 and T3 treatments were quit low development of both peroxide value (POV) and acid degree value (ADV) of fat during some stages of storage, which have retained their validity according to the scale of accepted level of POV and ADV as even after 4 weeks of storage period. The microbiology study reveled that there was no growth of yeast, Mold and Coliform bacteria in treatments and control PC at all period of storage while the total count of viable bacteria was less in PC of treatments than control PC and all of were in the limited scale of acceptance. Finally using CBM in processed cheese makes this dairy product useful as a functional food.